Spectral Seismic Analysis of Vertical Cylindrical Steel Tanks - Saint-Felix-López, Nelson; Álvarez-Deulofeu, Eduardo-Rafael; Candebat-Sánchez, Dario (Revista Facultad de Ingeniería, 2021)
The dynamic response results of a vertical cylindrical steel tank located in the south-eastern zone of the Republic of Cuba are analyzed. The tank was subjected to horizontal seismic excitation from the development of different calculation models, taking as reference the API 650 design code of 2013 and the parameters that characterize the seismic hazard of the Republic of Cuba established in the design code NC 46: 2017. In the investigation, two mathematical calculation models were implemented: a simplified one based on the equivalent mechanical system described by Housner in 1963 and a complex model, which integrates the finite element technique and the spectral modal analysis method with the help of the professional software SAP2000, v.22.0. When analyzing the research results, it was concluded that (1) the values ​​of periods in tanks are high due to the fluctuations of the stored fluid; (2) there is an agreement between the analytical method specified in API. 650 and computational models based on finite elements; (3) the model developed from finite elements corroborates the existence of deformations in the lower part of the tank walls, which is known as "elephant foot" and "diamond point", as well as buckling in the upper part of the sidewall of the tank caused by the effect of the waves; and (4) according to the aspect ratios considered (H/R), in which the radius tank is constant, the value of the convective period decreases as said aspect ratio decreases; becoming the less dominant impulsive mode.